Kebiasaan belajar siswa di era digital: Tantangan dan solusi guru dalam pembelajaran - Rahmatillah, Zahra (Maliki Interdisciplinary Journal, 2025)
Student learning habits in the digital age have changed significantly, driven by the availability of mobile devices and widespread internet access. Students now learn more through gadgets, social media, and online platforms, but this poses challenges such as digital distractions, low motivation, and access inequality. From the teachers' perspective, there are challenges in understanding digital literacy and facilitating technology-based learning. Additionally, disparities in access and digital skills among students impact the effectiveness of learning. This article discusses students' digital learning habits, the challenges faced by teachers, and solutions that can be implemented in the classroom. The proposed solutions include strengthening teachers' and students' digital literacy, using blended learning and active learning, implementing strategies to manage gadget distractions, and adapting multimodal learning channels. The hope is that teachers can become effective facilitators who ensure fair access and meaningful learning activities. This article includes concrete recommendations for school policies and teacher professional development.